Equipment Inventory Using Information Management Methods in the Crib Tool of the Medan State Polytechnic Mechanical Engineering Workshop - Handoko, Riki; Munthe, Hamzah Syahbana (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
To help businesses or organizations manage their inventory of goods more effectively and efficiently, information management is crucial. Businesses can monitor and manage the amount of goods on hand, prevent shortages or excess inventory, and streamline the shipping and receiving process with effective information management. Instead of utilizing a technology-based (computer-based) management system, the equipment management system in the Tool Crib of the POLMED mechanical engineering workshop is still conventional. wherein equipment borrowed by students or other stakeholders is not information management-based and is instead still documented in a form. Therefore, it is impossible to effectively control the quantity, quality, and identity of the tools that are borrowed. And the fact that the equipment is frequently misplaced or lost presents a challenge. The Waterfall method is the approach devised during the research. Software development follows a methodical design called the Waterfall Method. This study used quantitative descriptive research as its methodology. A method or approach to solving research problems in quantitative descriptive research involves characterizing the state of the object under investigation a person, organization, factory, etc. as it is based on real facts at the moment the research was conducted or is being conducted.